ROCKY MOUNTAIN RANGER DISTRICT TRAVEL MANAGEMENT PLAN, ROCKY MOUNTAIN RANGER DISTRICT, LEWIS AND CLARK NATIONAL FOREST, GLACIER, PONDERA, TETON, AND LEWIS AND CLARK COUNTIES, MONTANA. [Part 40 of 80] (EPA number: 050236, 386 pages and maps, June 9, 2005, 2005)
PURPOSE: The implementation of a travel management plan for the Rocky Mountain Ranger District of the Lewis and Clark National Forest, Glacier, Pondera, Teton, and Lewis and Clark counties, Montana is proposed. The new plan would address motorized and non-motorized travel on nonwilderness roads, trails, and areas of the district. Changing travel management would affect recreational opportunities (mileage and acreage) for use of motorized wheeled vehicles, snowmobiles, bicycles, stock, hiking, and other modes of travel on roads, trails, and cross-country routes. Five alternatives, including a No Action Alternative (Alternative 1), which would perpetuate the current management regime, are considered in this draft EIS. Major features of the plan include consideration of air, water and soil impacts, impacts to heritage resources, recreation access, protection of inventoried roadless and designated wilderness areas, socioeconomic aspects of the plan, transportation modes affected, and vegetation and wildlife habitat impacts. A preferred alternative will be identified in the final EIS. POSITIVE IMPACTS: The plan would provide the public with opportunities to use both nonmotorized and motorized modes of transportation to access public lands and travel on National Forest System lands, roads, and trails, while protection natural and cultural resources within the forest. The plan would ensure ample trail-related, off-highway-vehicle, and other motorized and nonmotorized recreational opportunities; provide a diversity of trail opportunities, including newly developed trails suitable for a variety of modes of travel; and ensure the transportation safety of users of the transportation system. NEGATIVE IMPACTS: Road, trail, and off-road use of motorized and nonmotorized vehicles would continue to undermine road and trail conditions and damage vegetation and wildlife habitat, including habitat for endangered and threatened species, as well as cultural resources; the latter would also be subject to a greater threat of vandalism due to improved accessibility. Erosion would be exacerbated along some routes, particularly those subject to an increase of passenger vehicle use. LEGAL MANDATES: National Forest Management Act of 1976 (16 U.S.C. 1600 et seq.).